The use of songs in History teaching. An alternative proposal to rote learning - Díaz Pérez, Adolfo Alejandro (2022)
The use of songs in the teaching of history represents a novel proposal that emerges as an alternative to rote learning that has traditionally been developed in this area of knowledge. The article is the result of a pedagogical practice developed in three teacher training courses of the Facultad de Educación e Idiomas de la Universidad Nacional Autónoma de Nicaragua, Managua (UNAN-Managua), where the strategy of song analysis was applied with the aim of assessing its impact on learning processes. This research is based on the systematization of experiences, it is qualitative in nature and techniques such as documentary review, interviews and focus group were used for the collection of information, in addition, the didactic proposal was validated by experts and a pilot test in two class groups. The results show that songs are a didactic resource that promotes participation, inferential comprehension levels, develops critical thinking and generates a new learning environment around history education in the classroom.